Low-cost small-scale irrigation for developing an agroforestry system in the semi-arid zone of Niger: case of the apple of the Sahel (Ziziphus mauritiana L.) - Traore, Bouba; Illiasso, Aboubacar D. K. T.; Soulé, Moussa; Arzika, Mahaman Zaharadine; Abdoussalam, Ibrahima; Moussa, Abdourazak Alio; Koudoussou, Ibrahim Mana; Moyo, Martin (Frontiers in Sustainable Food Systems, 2024)
Cultivation of the 'Apple of the Sahel' (also known as Indian Jujube) is central to the food security, nutrition, and income of rural communities in developing countries like Niger. However, rainfall variability significantly impacts the development of this plant. This study aims at determining the effects of seasonal water regimes on the growth and productivity of the Apple of the Sahel. The trials were conducted in 2020 and 2021 during the rainy and dry seasons at the ICRISAT experimental site of Sadore, Niamey, Niger. The experiment was arranged in a factorial design with three irrigation doses (D) and three irrigation systems (G) as main and subplot factors, respectively. The sub-subplot factors were irrigation frequencies (F) and growth boosters (B), each with two levels. In the dry season, irrigation dose application significantly (P = 0.001) increased soil volumetric water content (vwc). A similar increase in soil vwc was achieved under small-scale drip irrigation with an application of the same dose of organic material (P = 0.001). The diameter of the apple of Sahel trees significantly increased (P = 0.03) under the small-scale drip irrigation systems with 6.72 mm recorded under the two-drip irrigation system (G2) as compared with the manual system (G0). In dry season, the total fruit harvest of Apple of the Sahel recorded had increased (P = 0.04) under irrigated system, varying from 112% to 246% depending on the number of drippers and as compared with the manual system. These results highlight that small scale drip irrigation should be used in combination with appropriate water and fertilizer management to improve water availability and tree yield in agroforestry systems in the arid regions such as Niger.